Corporate social responsibility disclosure of Malaysian shariah public listed companies - Aziz, Muhamad Fikri; Haron, Razali (2020)
Corporate social responsibility disclosure (CSRD) is a crucial tool for communicating with stakeholders regarding a company's social responsibility activities. This research aims to examine the level of CSRD of top 50 of Malaysian Shariah Public Listed Companies (MSPLCs) listed in the Bursa Malaysia from 2007 to 2017. The level of disclosure is measured using newly developed content analysis. The results show that the level of CSRD of MSPLCs is increasing but still at a low level. The "community" theme is the most CSR items disclosed, while "marketplace" theme is the least CSR item disclosed in the annual report. There is a need further encouragement from the government, NGOs or Bursa Malaysia to attract all PLCs in Malaysia to disclose their CSR activities in the annual report.